Responses of a scatter-hoarding rodent to seed morphology: links between seed choices and seed variability - Muñoz, Alberto; Bonal, Raul; Espelta, Josep Maria (Animal Behaviour, 2012)
Seed preferences of scatter-hoarding granivores may inﬂuence the evolution of seed traits in plants. However, there is little evidence linking the granivores’ responses to speciﬁc seed traits to the variability of seeds in a single plant species. This information is essential for understanding how the decisions of granivores can shape plant life histories. We analysed how seed morphology (size and shape) of the Holm oak, Quercus ilex, inﬂuences seed choices of the seed-disperser, the Algerian mouse, Mus spretus. We studied the seed variability of the oak and whether the frequency of seed phenotypes matched the seed choices of the disperser. The probabilities of seed removal decreased as the seeds became larger and more bullet-shaped, so that seeds that were simultaneously large and bullet-shaped had the lowest probabilities of being dispersed. These seeds are probably refused by rodents because they impose higher handling and transport costs. The size and shape of the Holm oak seeds were highly variable between trees, but extraordinarily consistent within a single tree over different years. However, the analysis of seed variability revealed a disproportionately low frequency of large bullet-shaped phenotypes, which are those barely removed by rodents. Seed preferences of dispersers of species with high seed variability between trees can lead to differences in the chances of seeds produced by different trees being dispersed. Those seed phenotypes preferred by dispersers could make a higher contribution to the next generation, which could inﬂuence the evolution and variability of seeds in a plant species
Keywords: acorn; Algerian mouse; animal-plant interaction; handling cost; hoarding behaviour; Holm oak; Mus spretus; Quercus ilex; seed caching; small rodent

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae